OPTIMIZATION OF DIMETHYL SULFOXIDE AS AN ENHANCER ON EX VIVO PENETRATION OF SESEWANUA (CLERODENDRUM FRAGRANS WILD) LEAF EXTRACTS EMULGEL - PANGALO, PAULUS; SAPIUN, ZULFIAYU; IMRAN, ARLAN K.; MUINDAR; SABARUDDIN; WICITA, PRISCA SAFRIANI; YSRAFIL; MOHAMAD, FIHRINA (International Journal of Applied Pharmaceutics, 2022)
Objective: The present study aims to investigate the effect of using DMSO as an enhancer on the ex vivo penetration of an emulgel from sesewanua leaf extracts. Methods: The sesewanua emulgel was prepared into four formulas, SWE1-SWE4, with different DMSO concentrations: 0%, 3%, 5%, 7%, and compared with QCE, quercetin without DMSO. Further, the penetration test of the sesewanua leaf ethanol extract emulgel was performed by determining the rate and cumulative penetration of quercetin within the skin of the mice by employing the Franz diffusion cell approach. Results: The SWE4 emulgel containing 7% of DMSO was the best formula that enhanced the penetration of the emulgel, with a cumulative penetration at 331.423 mg/cm2, the penetration rate at 2.762 µg/cm2/minute, and better dispersibility of 4.6 cm and the results of the one-way ANOVA suggested a significant influence (p<0.05). DMSO with a concentration of 7% of the sesewanua emulgel was proven to increase 2,4-fold the rate and cumulative amount penetration. DMSO can be considered as a penetration enhancer of natural compounds for anti-inflammatory treatment. Conclusion: The use of natural ingredients as topical anti-inflammatory continues to be developed to avoid the first-pass effects. The used of DMSO in topical emulgel preparation become a simple way to enhance the penetrant of active inggredient.